2012
DOI: 10.1364/ol.37.004212
|View full text |Cite
|
Sign up to set email alerts
|

Clear coherent imaging in turbid microfluidics by multiple holographic acquisitions

Abstract: Recently it has been demonstrated that digital holography is a powerful means allowing imaging of both amplitude and phase objects in turbid flowing media. However, in quasi-static turbid microfluidics, multiple scattering contributions through the colloids superimpose coherently to the recording device, resulting in speckle noise and hindering a clear vision of the objects. In this Letter we exploit the Brownian motion of the colloidal particles to get multiple uncorrelated holograms, and we combine them to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 11 publications
1
39
0
Order By: Relevance
“…2(c)] was used to reduce speckle noise and multiple scattering on quasistatic turbid microfluidics of phospholipid particles. 4 Spatial noise 11 (fluctuations among the pixels in one image) was calculated as the standard deviation of pixels from the area that does not contain cells (background) in …”
Section: Image Acquisition and Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…2(c)] was used to reduce speckle noise and multiple scattering on quasistatic turbid microfluidics of phospholipid particles. 4 Spatial noise 11 (fluctuations among the pixels in one image) was calculated as the standard deviation of pixels from the area that does not contain cells (background) in …”
Section: Image Acquisition and Processingmentioning
confidence: 99%
“…It has already been demonstrated that imaging through scattering media and turbid liquids is possible by digital holography. [1][2][3][4][5][6][7][8][9][10][11] Separate holographic methods have been used for imaging through different turbid media, such as rotating diffuser, 1 onion cell layer and cornea, 2 milk, 3,4 ground-glass diffuser, [5][6][7] intralipid suspension, 8 and biological tissue. 9 However, a coherence-controlled holographic microscope 6 (CCHM) invented and built by our group provided low-coherence mode with improved coherence gate effect 7 (CGE).…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] Imaging through complex media, hologram denoising, and resolution enhancement are among the most investigated issues in DH. [8][9][10][11][12][13][14][15][16] The capabilities offered by DH microscopy turns out to be particularly useful for LoC studies. In particular, out-of-focus DH recordings can be performed while letting a multitude of objects flow inside the channel, thus occupying various positions along the optical axis.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of turbid media made of colloidal solutions, or live selfpropelling biological elements like e.g. bacteria, we proposed to tackle the imaging problem relying on Multi-Look Digital Holography (MLDH 8,13,14,[21][22][23][24] ). The disturbance due to turbidity can be treated as a speckle noise, and speckle reduction strategies were demonstrated to be successfully applicable to restore clear imaging through both quasi-static 8 and flowing colloidal solutions, 5,21,24 as well as liquid volumes filled with highly concentrated bacteria suspensions.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the method results in the projected image blurred while reducing the speckle contrast, and largely increases the difficulty for the screen fabrication. Bianco et al investigate how the velocity of moving medium affects the Doppler shift, thereby reducing speckle noise without degrading the image resolution [14], [15].…”
Section: Introductionmentioning
confidence: 99%